Paroxysmal Paralytic Attacks Secondary to Excessive Cola Consumption - Dubey, Divyanshu (Clin Med Res, 2014)
We report a rare case of cola-induced hypokalemia presenting as recurrent attacks of lower extremity weakness and falls. Excessive consumption of cola-based drinks has been associated with dental enamel erosion, obesity, and diabetes. There are very few published cases depicting the correlation between cola drinks and hypokalemic manifestations. In our patient an extensive workup was performed, and common causes were ruled out before making the diagnosis of cola-induced hypokalemia. Improvement in the patient’s symptoms and electrolyte levels after reducing the consumption of cola-based drinks further confirmed our diagnosis. This case also emphasizes the importance of obtaining a detailed history and consideration of broad differential diagnoses in identifying uncommon but reversible etiologies.